Snowmelt runoff analysis and modeling for the upper Cache la Poudre River basin, Colorado - Richer, Eric E., author; Kampf, Stephanie K., advisor; Fassnacht, Steven R., committee member; Arabi, Mazdak, committee member (Colorado State University. Libraries, 2009)
The Cache la Poudre River is a vital water source in Northern Colorado, and it exhibits high variability in annual water yield. This research examines sources of variability in snowmelt runoff as a means of identifying methods that could help improve streamflow prediction for the basin. The objectives of this thesis are to: (1) develop a naturalized flow record for the river and determine the effects of flow modification on the magnitude and timing of discharge; (2) analyze relationships between snow cover distributions and naturalized discharge to identify important areas for runoff production; and (3) evaluate the ability of the Snowmelt Runoff Model (SRM) to simulate seasonal hydrographs. Naturalized flow records were developed by accounting for all diversions from the river, inputs of foreign water via trans-basin diversions, and reservoir operations. Moderate Resolution Imaging Spectroradiometer (MODIS) 8-day snow cover products were obtained for the snowmelt season, mid-March through June, from 2000-2006. Snow cover depletion was analyzed within spatial subsets of sub-basins and elevation zones, and regression analyses were used to compare snow covered area (SCA) to naturalized discharge (Q). To investigate spatial and temporal snow distribution trends, probability of snow cover datasets were derived, which show the frequency of snow cover for different parts of the basin. Using these SCA data, the SRM was then configured to simulate snowmelt runoff hydrographs for the basin using both optimized and standard sets of model parameters. Daily hydrographs were simulated from March 1 to September 30 for each year in the 2000-2006 study period. Results show that flow modification delayed hydrograph timing and reduced water yields for all years included in the study period. The naturalized hydrograph displayed a wide range of relationships to SCA depletion patterns in the basin. At low and high elevations in the basin, SCA patterns had poor relationships to naturalized discharge. Snow cover depletion in middle elevations, however, had a much stronger relationship to discharge, with steady snow cover depletion occurring in these areas during hydrograph rise. Snow cover analyses point to strong elevation dependence in runoff generation, with most runoff coming from a small area in the basin above a mid-elevation snow cover transition zone. Snow cover data prove useful for configuring snowmelt runoff simulations, and the SRM simulated seasonal hydrographs with good model performance (Nash-Sutcliffe coefficient of efficiency > 0.9) when calibrated to the naturalized hydrographs for individual years. This suggests that the SRM could be used to generate seasonal streamflow forecasts given appropriate selection of parameter values and input variables. These conclusions all point to the utility of long-term snow cover datasets for improved water resources planning and management in snowmelt dominated mountain basins.
Department Head: Michael J. Manfredo.